APPLICATION OF HIERARCHICAL CLUSTERING ALGORITHM FOR STRUCTURAL CHARACTERISTIC OF MOVING PHYSICAL OBJECTS - Babenko, N.I. (Journal of Information Technologies in Education (ITE), 2015)
Approach to the development of management solutions using the cluster analysis can qualitatively improve the management system by moving objects through the adequate response to the impact of the key factors influencing the characteristics of physical objects. The aim is to attempt to solve the problem of identifying key factors and physical signs of moving physical objects needed to make appropriate management decisions by using cluster analysis. The article defines the types of clustering algorithms; the system of information parameters directly or indirectly characterizing the analyzed characteristics is emphasized, hierarchical and non-hierarchical cluster analysis methods are considered. The research finding is the construction of tree diagram using the program STATISTICA 8,which gives the idea of possible clusters’ number combining physical indicators under the dynamic changes of moving objects. The advantage of cluster analysis usage is the use of factors relating to both internal and external environments of the physical properties’ interaction of moving objects.